2021
DOI: 10.4018/978-1-7998-4099-2.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Concept of Approach to Optimize ICT Management Practices

Abstract: The rapid evolution of information and communication technologies (ICT) has led to changes in business processes, namely in public services or in local administration. Currently, customer expectations are focused on an incremental modernization that may imply greater mobility, cost reduction, and response times. This chapter describes a multidisciplinary and integrative approach considering the specificity of the Portuguese local administration. The proposed approach assumes of continuous improvement within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…This virtualized model can be a way to reduce costs with maintenance contracts, enhance increased information security and internal know-how in the maintenance and configuration tasks of the virtual plant. In the context of this evaluation phase, it is also intended to ensure the ubiquity of access, between the various buildings, decentralized throughout the county, providing the data on impressions to ensure greater mobility of people and autonomy daily [17]. Particularly relevant are the two final tasks in this Phase 1: the evaluation of ease of management and environmental improvement, always present throughout this project the environmental preservation and the use of technologies that allow this preservation, in alignment with Green IT; and the containment equation or whenever possible, cost reduction without compromising the project [17].…”
Section: Qualitative Components Of the Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…This virtualized model can be a way to reduce costs with maintenance contracts, enhance increased information security and internal know-how in the maintenance and configuration tasks of the virtual plant. In the context of this evaluation phase, it is also intended to ensure the ubiquity of access, between the various buildings, decentralized throughout the county, providing the data on impressions to ensure greater mobility of people and autonomy daily [17]. Particularly relevant are the two final tasks in this Phase 1: the evaluation of ease of management and environmental improvement, always present throughout this project the environmental preservation and the use of technologies that allow this preservation, in alignment with Green IT; and the containment equation or whenever possible, cost reduction without compromising the project [17].…”
Section: Qualitative Components Of the Frameworkmentioning
confidence: 99%
“…In the context of this evaluation phase, it is also intended to ensure the ubiquity of access, between the various buildings, decentralized throughout the county, providing the data on impressions to ensure greater mobility of people and autonomy daily [17]. Particularly relevant are the two final tasks in this Phase 1: the evaluation of ease of management and environmental improvement, always present throughout this project the environmental preservation and the use of technologies that allow this preservation, in alignment with Green IT; and the containment equation or whenever possible, cost reduction without compromising the project [17]. Phase 2, as summarized in Figure 3, begins with the Study and Planning, having been concluded the assessment of the constraints encountered, the needs for improvement, and upgrade of the solution.…”
Section: Qualitative Components Of the Frameworkmentioning
confidence: 99%
See 3 more Smart Citations